Meningkatkan Keterampilan Berpikir Kritis Fisika Siswa Melalui Model Pembelajaran Kooperatif Tipe STAD - Halmuniati, Halmuniati; Isa, La; Asmin, La Ode; Wui, La (Jurnal Penelitian Pendidikan Fisika, 2021)
This research was conducted with the aim of knowing the improvement of students' critical thinking skills through the STAD type cooperative learning model. This research was carried out on Class XI students of SMK Negeri 1 Mananggu, Gorontalo Province in the odd 2019/2020 academic year. The research used is classroom action research. There were 17 students who took part in the classroom action research, consisting of 7 boys and 10 girls, who on average had moderate abilities in physics subjects with a learning completeness level between 41.2% - 64.8%. The results of the study prove that the use of the STAD type cooperative model is able to improve students' critical thinking skills on static fluid material. The results of the analysis show that in the first cycle of learning, the results obtained are from 17 students only 11 people or 63.53% who get mastery learning, experiencing an increase in learning outcomes in the second cycle of 19.56% so that students who experience learning mastery reach 14 people. or 83.09%.